Analysis of Liquidity And Solvability Ratios In Assessing The Ability To Pay Obligations At PT Pegadaian Using An Islamic Accounting - Nur Yanti; Muhammad Fakhri Amir; Masyhuri Masyhuri (Journal of Management and Business Innovations, 2026)
This study evaluates PT Pegadaian's ability to fulfill its short- and long-term financial obligations through liquidity and solvency analysis for the 2020–2024 period. The novelty of this research lies in its dual-perspective framework, integrating conventional financial ratio analysis with Islamic accounting values to assess both financial stability and Sharia compliance. A mixed-method approach with a convergent parallel design was employed, combining quantitative analysis of liquidity and solvency ratios with qualitative analysis based on Islamic accounting literature. Data were obtained from PT Pegadaian’s annual financial reports published on the company’s official website. The findings indicate that the Current Ratio ranged from 149.7% to 173.8%, reflecting a healthy liquidity position, while the Quick Ratio ranged from 148.5% to 172.5%, indicating healthy to very healthy performance. However, the Cash Ratio remained below the ideal standard, ranging from 0.57% to 1.43%, suggesting limited cash relative to current liabilities. Regarding solvency, the average Debt-to-Asset Ratio of 62.5% indicates a relatively healthy financial condition, whereas the Debt-to-Equity Ratio ranged from 150.5% to 190.5%, reflecting high reliance on external financing. From an Islamic accounting perspective, PT Pegadaian has implemented the principles of trustworthiness, transparency, and responsibility, although the principle of tawazun in its capital structure has not been fully achieved. Keywords: Ability to Pay Obligations, Islamic Accounting, Liquidity Ratio, Solvability Ratio